PENGARUH MELATONIN TERHADAP PROFIL LIPOPROTEIN TIKUS PUTIH (Rattus norvegicus L.) HIPERLIPIDEMIA = THE EFFECT OF MELATONIN TO LIPOPROTEIN PROFILE OF RAT ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The effect of melatonin to lipoprotein profile of rat (Rattus norvegicus L.) with hyperlipiÂ¬demia were studied. A total of forty two adult male rat were used. The rat were devided to seven groups. Three groups as the controls, which are